Nonlinear optical response of graphene in terahertz and near-infrared frequency regime - ANG, Yee Sin; CHEN, Qinjun; ZHANG, Chao (Frontiers of Optoelectronics (Online), 2015)
In this review, we discuss our recent theoretical work on the nonlinear optical response of graphene and its sister structure in terahertz （THz） and near-infrared frequency regime. Due to Dirac-like linear energymomentum dispersion, the third-order nonlinear current in graphene is much stronger than that in conventional semiconductors. The nonlinear current grows rapidly with increasing temperature and decreasing frequency. The third-order nonlinear current can be as strong as the linear current under moderate electric field strength of 104 V/cm. In bilayer graphene （BLG） with low energy trigonal warping effect, not only the optical response is strongly nonlinear, the optical nonlinearity is well-preserved at elevated temperature. In the presence ofa bandgap （such as semihydrogenated graphene （SHG））, there exists two well separated linear response and nonlinear response peaks. This suggests that SHG can have a unique potential as a two-color nonlinear material in the THz frequency regime where the relative intensity of the two colors can be tuned with the electric field. In a graphene superlattice structure of Kronig-Penney type periodic potential, the Dirac cone is elliptically deformed. We found that not only the optical nonlinearity is preserved in such a system, the total optical response is further enhanced by a factor proportional to the band anisotropy. This suggests that graphene superlattice is another potential candidate in THz device application.